MANAGING THE HUMAN RESOURCES IN BEER INDUSTRY - Živković, Dragić; Gučanin, Suzana; Jež, Zdravko (Economics of Agriculture, 2014)
The human resources management in business systems comprises a selection of goals, a policy determination, as well as planning, organizing, coordination and control of activities in the fled of human resources, by taking over the management actions, in order to achieve the selected goals and to realize the purpose of the management function, as a sub-system of an organizations operation. The basic tasks of the human resources management are: planning, knowledge managing, improvement of work process and quality, control and evaluation of achievements. The papers goal is to point out to a significance, which it has for its successful business, according to an analysis and description of the most important activities of the human resources management, as theoretically, as well as practically, in a concrete business system.